NEW ASPECTS OF EDUCATIONAL DEVELOPMENT OF SOCIETY - Kravchuk, Oleksandr; Lykhova, Sofiia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Review of the monograph "Convergence of the Solar Knowledge Society: Creative Education and Civilizational Development". Reviewers note that modern creative education, science and practice of the new millennium require the use of critical thinking tools, tools, methods of special decision analysis and situational management technologies to respond to both typical and crisis situations. The eternal landmark of civilizational development, of course, is the solar society of knowledge. Therefore, the convergence of the solar knowledge society, which is respectfully considered in the pages of the monograph, is a powerful educational platform, a solar beacon of civilization, which lays solid foundations - conceptual foundations of eternal ideas, dreams, images of education and science in modern Ukraine. -philosophical guidelines of humanity, justice, professionalism, readiness to defend the Fatherland and situational management of response to both typical and crisis situations in Ukraine, Europe and the world at large. The publication is intended for educators, scientists, philosophers, lawyers, sociologists, educators, psychologists, security scientists, cyberneticists, students, graduate students and doctoral students, as well as anyone interested in critical thinking tools, special analysis methods and educational Grid and Blockchain situational management technologies. on crisis situations.